Предмет: Геометрия,
автор: z019ah
срочно, помогите пожалуйста!!!!!!
Приложения:
Ответы
Автор ответа:
6
Ответ:
6
Объяснение:
S = S прямоугольника - (S1 + S1 + S2)
S прямоугольника = 6 ∙ 4 = 24
S треугольника = 1/2 основание ∙ высоту
S1 + S1 + S2 = 1/2 ∙ 3 ∙ 4 + 1/2 ∙ 3 ∙ 4 + 1/2 ∙ 6 ∙ 2 = 6 + 6 + 6 = 18
S = S прямоугольника - (S1 + S2 + S3) = 24 - 18 = 6
Похожие вопросы
Предмет: Математика,
автор: dasafedorenko378
Предмет: Математика,
автор: reygen
Предмет: Математика,
автор: savchukanna1282
Предмет: Алгебра,
автор: isterikaelka